Standardization of an Ash (Fraxinus excelsior) Pollen Allergen Extract - Hrabina, Maud; Purohit, Ashok; Oster, Jean-Philippe; Papanikolaou, Ioanna; Jain, Karine; Pascal, Poncet; Sicard, Hubert; Gouyon, Brigitte; Moingeon, Philippe; Pauli, Gabrielle; André, Claude (International Archives of Allergy and Immunology, 2007)
Background: Ash tree (Fraxinus excelsior) is the main representative of the Oleaceae family in temperate zones. Diagnosis of ash pollen allergy is made difficult due to (1) an overlapping pollinization period with Betulaceae, (2) non-inclusion in current diagnostic assays, and (3) some cross- reactivity with minor allergens from Betulaceae. The aim of this study was to calibrate an ash pollen in-house reference preparation (IHRP) in allergic patients in order to produce standardized products for diagnosis and immunotherapy purposes. Methods: Ash pollen IHRP was extracted, ultrafiltered and freeze dried. Allergens in the extract were detected after 2-dimensional PAGE using specific sera and a monoclonal antibody. The Fra e 1 content of IHRP was evaluated by quantitative immunoprint. Forty-eight subjects from the North-East of France exhibiting clinical symptoms, a positive skin test and specific IgE levels ≧class 2 to ash pollen were recruited. IgE immunoprints were performed to select patients sensitized to the ash Fra e 1 allergen as opposed to cross-reacting allergens. Serial 10-fold dilutions of the IHRP were tested by skin prick tests in order to determine the concentration inducing a geometrical mean wheal diameter of 7 mm, said to correspond to an index of reactivity (IR) of 100 per millilitre. Results: IgE-reactive molecules in IHRP comprise Fra e 1, Fra e 2, a 9-kDa molecule (presumably Fra e 3), as well as a doublet at 15 kDa and high molecular weight allergens. The 100 IR concentration of IHRP inducing a geometrical mean wheal diameter of 7 mm in 22 patients sensitized to Fra e 1 corresponds to the 1/126 (w/v) extraction ratio (i.e. 259 µg/ml of protein by Bradford) and contains 17 µg/ml of Fra e 1. The variability in total activity of 5 batches of standardized extracts was found to be significantly reduced when compared with 7 non-standardized extracts. Conclusion: An ash pollen IHRP was defined and molecularly characterized. Its successful standardization at 100 IR/ml in patients specifically sensitized to Fra e 1 allowed a skin reactivity-based calibration in properly diagnosed patients. Such a standardized ash pollen extract is a reliable tool to support immunotherapy of ash pollen allergy.